One day one story di RA Nawa Kartika: Upaya Membangun Karakter Melalui Literasi Sejak Usia Dini - Devi Fitriah Islamiyah; Siti Hofifah; Fida Annur; Robiatul Adawiyah (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
This study examines the impact of the "One Day One Story" (ODOS) program on enhancing children's literacy, including reading, writing, speaking, imagination, and critical thinking skills. Regular activities of reading and listening to stories have been proven effective in improving literacy. Using qualitative methods and case studies, the research demonstrates that children participating in the ODOS program show significant increases in their interest and motivation to read, contributing to their overall literacy development. The program extends beyond the technical aspects of literacy by introducing cultural and moral values embedded in the stories, which foster character development. The study also emphasizes the crucial role of parental involvement in supporting literacy activities at home. Active participation from parents and access to high-quality reading materials help create an environment conducive to literacy growth. The research recommends integrating the ODOS program into school curricula to enhance student engagement. By leveraging digital technology, the program can be adapted to meet the needs of modern education, offering a more interactive and engaging learning experience. The findings highlight the importance of collaboration among parents, teachers, and communities in creating a supportive learning environment that promotes the holistic development of children's literacy skills.